Gyromagnetic ratios and octupole collectivity in the structure of the $^{90-96}Zr isotopes - Stuchbery, A.E.; Benczer-Koller, N.; Kumbartzki, G.; Mertzimekis, T. J. (Phys. Rev. C, 2004)
Shell model calculations have been performed for low-excitation states in the Zr isotopes between 90Zr and 96Zr with an emphasis on the g factors and electromagnetic decay rates for the lowest 2+ and 3- states. Overall the 2+ states are reasonably well described. In contrast, the 3- states present a puzzle because the measured g factors imply a single-particle configuration whereas the experimental E3 transition rates imply collective structures that cannot be explained by shell model calculations. A consistent description of the 3 - states in 90Zr and 96Zr is sought in terms of coupling between the single-particle structure and a collective octupole vibration.